Using Multidisciplinary Focus Groups to Inform the Development of mI SMART: A Nurse-Led Technology Intervention for Multiple Chronic Conditions - Jennifer A. Mallow; Laurie A. Theeke; Elliott Theeke; Brian K. Mallow (Nursing Research and Practice)
Used as integrated tools, technology may improve the ability of healthcare providers to improve access and outcomes of care. Little is known about healthcare teams’ preferences in using such technology. This paper reports the findings from focus groups aimed at evaluating a newly developed primary care technology platform. Focus groups were completed in academic, outpatient, and community settings. Focus groups were attended by 37 individuals. The participants included professionals from multiple disciplines. Both prescribing (N=8) and nonprescribing healthcare team members (n=21) completed the focus groups and survey. The majority were practicing for more than 20 years (44.8%) in an outpatient clinic (62%) for 20–40 hours per week (37.9%). Providers identified perceived obstacles of patient use as ability, willingness, and time. System obstacles were identified as lack of integration, lack of reimbursement, and cost. The positive attributes of the developed system were capability for virtual visits, readability, connectivity, user-friendliness, ability to capture biophysical measures, enhanced patient access, and incorporation of multiple technologies. Providers suggested increasing capability for biophysical and symptom monitoring for more common chronic conditions. Technology interventions have the potential to improve access and outcomes but will not be successful without the input of users.